2013
DOI: 10.2190/ec.49.4.a
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Effects of Interactive versus Didactic Pedagogy Using Computer-Assisted Instruction

Abstract: This article reports on the results of a representative sample meta-analysis that explored the effects of interactive versus didactic pedagogy using computerassisted instruction on measures of academic achievement. A systematic literature search revealed 40 studies, from which 55 effect sizes were extracted. The random effects model of analysis of these effect sizes revealed that the overall positive mean effect size of 0.175 was significantly different from zero; indicating that, on average, students receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(42 reference statements)
4
1
0
Order By: Relevance
“…The inclusion criteria immediately excluded articles that were only concerned with the technical construction of the affective EPAs (e.g., Sabourin, Mott, & Lester, 2011), studies with qualitative research results, such as from interviews and user observation (e.g., Andrade, Bagri, Zaw, Roos, & Ruiz, 2010), and studies in which the required descriptive statistics could not be obtained (e.g., Mumm & Mutlu, 2011). In the end, 30 studies remained, which is comparable in number with previous review studies (Thomas, Alexander, Jackson, & Abrami, 2013).…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…The inclusion criteria immediately excluded articles that were only concerned with the technical construction of the affective EPAs (e.g., Sabourin, Mott, & Lester, 2011), studies with qualitative research results, such as from interviews and user observation (e.g., Andrade, Bagri, Zaw, Roos, & Ruiz, 2010), and studies in which the required descriptive statistics could not be obtained (e.g., Mumm & Mutlu, 2011). In the end, 30 studies remained, which is comparable in number with previous review studies (Thomas, Alexander, Jackson, & Abrami, 2013).…”
Section: Methodssupporting
confidence: 80%
“…In the end, 30 studies remained, which is comparable in number with previous review studies (Thomas, Alexander, Jackson, & Abrami, 2013).…”
Section: Inclusion Criteriasupporting
confidence: 78%
“…The percentage of learning completeness that reaches 90 % supports this statement. This finding is also consistent with the results of Thomas et al (2013) and Suleman et al (2017) which concluded that CAI-based learning could motivate and improve students' achievement. However, the other side of success is that respondents generally feel that they are bored in the final stages of knowledge because the process of completing a learning session is too long.…”
Section: Assessing the Effectiveness Of The Cai Modelsupporting
confidence: 92%
“…The learning and training scenario models offered in the CAI algorithm much motivate students, so that students' understanding of a particular learning theme achieves 90% completeness, consistent with the findings of Thomas et al (2013) and Suleman et al (2017). Another finding of this study, some students stated that they still needed instructors (assistants) to get a deeper explanation when they failed to understand certain parts of interactive learning-based material.…”
Section: F I N D I N G Ssupporting
confidence: 77%